Ultimate Tic-Tac-Toe Bot Techniques - Brycen Addison; Michael Peeler; Chris Alvin (Proceedings of the International Florida Artificial Intelligence Research Society Conference, 2022)
In this work, we consider the game Ultimate Tic-Tac-Toe. We apply different bot-based strategies for play and compare their effectiveness, including: random play, a heat-map approach, Monte Carlo Tree Search, and functionality similar to AlphaZero. Our work reveals another game that AlphaZero crushes the competition.